Two New Neutrophil Subsets Define a Discriminating Sepsis Signature - Meghraoui-Kheddar, Aïda; Chousterman, Benjamin G.; Guillou, Noëlline; Barone, Sierra M.; Granjeaud, Samuel; Vallet, Helene; Corneau, Aurélien; Guessous, Karim; de Roquetaillade, Charles; Boissonnas, Alexandre; Irish, Jonathan M.; Combadière, Christophe (American journal of respiratory and critical care medicine, 2022)
Sepsis is the leading cause of death in adult ICUs. At present, sepsis diagnosis relies on nonspecific clinical features. It could transform clinical care to have immune-cell biomarkers that could predict sepsis diagnosis and guide treatment. For decades, neutrophil phenotypes have been studied in sepsis, but a diagnostic cell subset has yet to be identified. To identify an early, specific immune signature of sepsis severity that does not overlap with other inflammatory biomarkers and that distinguishes patients with sepsis from those with noninfectious inflammatory syndrome. Mass cytometry combined with computational high-dimensional data analysis was used to measure 42 markers on whole-blood immune cells from patients with sepsis and control subjects and to automatically and comprehensively characterize circulating immune cells, which enables identification of novel, disease-specific cellular signatures. Unsupervised analysis of high-dimensional mass cytometry data characterized previously unappreciated heterogeneity within the CD64 immature neutrophils and revealed two new subsets distinguished by CD123 and PD-L1 (programmed death ligand 1) expression. These immature neutrophils exhibited diminished activation and phagocytosis functions. The proportion of CD123-expressing neutrophils correlated with clinical severity. This study showed that these two new neutrophil subsets were specific to sepsis and detectable through routine flow cytometry by using seven markers. The demonstration here that a simple blood test distinguishes sepsis from other inflammatory conditions represents a key biological milestone that can be immediately translated into improvements in patient care.